The Influence of Food Marketing on Children's Dietary Choices (International Journal of Food and Nutritional Sciences, 2022)
This abstract explores the intricate interplay between food marketing, media, and their profound influence on individual food intake and broader dietary patterns. In the contemporary landscape, visual appeal and strategic branding in food marketing capture consumer attention, shaping perceptions of taste and desirability. Advertising exposure, both through traditional and digital channels, significantly impacts the consumption of energy-dense, nutrient-poor products. Promotional strategies, such as discounts and limited-time offers, contribute to increased intake of specific food items. The rise of digital and social media amplifies these influences, with platforms, influencers, and content creators shaping consumer preferences and driving dietary choices. Product placement in media subtly integrates food products into entertainment content, impacting viewers' preferences. Psychological triggers, including emotions and social norms, play a pivotal role in creating positive associations with specific food products. The portrayal of food in media, celebrity endorsements, online reviews, and targeted marketing based on demographic factors further contribute to the complexity of these influences. As these dynamics continue to evolve, responsible marketing practices, increased media literacy, and regulatory measures are essential to promote healthier dietary choices and safeguard public health. Understanding the multifaceted nature of food marketing and media is crucial for developing comprehensive strategies that address the complex relationship between marketing, media, and individual food consumption patterns.